The effect of leadership, motivation, and work discipline on the employees performance of finance section in the regional working unit in Tulungagung regency - Rista Eka Rachim Febiningtyas; Diah Ekaningtias (STIE Perbanas Surabaya, 2014)
The role of local government has been increasing significantly since the enactment of regional autonomy by the central government. In this case, the majority of central government authorities are delegated to each local government. Consequently, the success of development and economy of the region depends largely on the local government concerned. The performance of local governance will run well, if there is adequate government apparatus that support the local government activities. The good performance of the government apparatus will have an impact on the achievement of goals and responsibilities of the local government, the central government and the public. Therefore, the purpose of this study is to find out whether variables of leadership, motivation and work discipline can affect the performance of employees of finance section in the regional working units of Tulungagung Regency. The samples in this study are the employees of finance section in the Regional Working Units of Tulungagung Regency. Based on the multiple linear regression analysis test, it can be concluded that the variables of leadership and work discipline have significant effect on the performance of employees, while the variable of motivation does not have significant effect on the performance of employees of finance section in the Regional Working Units of Tulungagung Regency.